Qualidade fisiológica e físico-química de grãos e sementes de feijão carioca e feijão preto armazenados em atmosfera controlada em temperaturas elevadas - Berghetti, Magno Roberto Pasquetti (2020)
Common bean (Phaseolus vulgaris L.) it is among the prominent crops in Brazil and in the world due to the large extension of cultivated area and also its socioeconomic importance, as a source of protein, among other nutrients in human food. Although there are several ways to store beans, still much of the physiological quality and physical quality are lost after harvest due to inadequate conditions used throughout storage. The aim this work was to evaluate the effect of low oxygen partial pressures (O2) and high carbon dioxide (CO2), combined with different temperatures on the maintenance of physiological potential of seeds and physicochemical characteristics of bean grains. In 2018, FEPAGRO 26 and FEPAGRO Garapiá seeds were maintained for 7 months under the following conditions: [1] ambient; [2] 1.0 kPa O2 + 0.04 CO2; [3] 2.0 kPa O2 + 0.04 CO2; [4] 2.0 kPa O2 + 30.0 kPa CO2; [5] 2.0 kPa O2 + 80.0 CO2. In 2019, cultivars FEPAGRO 26, FEPAGRO Garapiá and FEPAGRO Triunfo were used, whose seeds were maintained for 7 months under the following conditions [1] ambient; [2] 1.0 kPa O2 + 0.04 CO2; [3] 1.0 kPa O2 + 15.0 CO2; [4] 1.0 kPa O2 + 30.0 CO2; [5] 2.0 kPa O2 + 0.04 kPa CO2, at temperatures of 20, 25 and 30 °C. The analyses performed in this work were: standard germination test, sand emergence, field emergence, shoot and root length, dry and fresh mass, electrical conductivity, moisture content, cooking time, tegument luminosity, grain weight, protein content and infestation by Acanthoscelides obtectus. The highest germination percentage is used with the use of partial pressures of 1.0 kPa of O2 in seeds stored at 20 °C. The use of high partial pressure of CO2 for the cultivars FEPAGRO Garapiá, FEPAGRO 26 and FEPAGRO Triunfo after 7 months of storage, did not provide effect when low pressure of 1.0 kPa of O2. The cooking time was lower in storage under controlled atmosphere conditions at a temperature of 20 °C, and the higher cooking time occurred under conditions stored at a temperature of 30 °C. The storage in a controlled atmosphere, at temperatures of 20, 25 and 30 °C, maintain high luminosity in all tested cultivars and protein contents equal to or greater than the ambient condition tested after 7 months of storage.